Asuhan Kebidanan Continuity of Care (COC) pada Ny “S” 39 Tahun di Puskesmas X Kecamatan X - Susiani Heny; Hapsari Windayanti (Universitas Ngudi Waluyo, 2025)
There were 3 main causes of maternal death in 2021, namely bleeding with 7 cases, hypertension in pregnancy with 2 cases, the most deaths occurred during the postpartum period (10 cases), pregnancy (6 cases), and the delivery process (4 cases) (Semarang Regency Health Office, 2021). The causes of frequent MMR cases are usually due to lack of access to quality health services, especially timely emergency services, which are caused by late recognition of danger signs and decision making, delays in reaching health facilities, and delays in receiving services at health facilities. In addition, the causes of maternal death cannot be separated from the condition of the mother herself and are one of the 4